The lost half. Quantitative methods and historical studies: a critical review Michele Nani* - Nani, Michele (Italia Contemporanea - Sezione Open Access, 2021)
Starting from three recent publications (a handbook, a conference proceeding, and an edited volume), this article discusses the limited use of quantitative methods among historians, especially in the Italian context, despite the widespread debate about digital history and historical “big data”. After the great promises made between the 1960s and the 1980s, and the opposite trend of the following 20 years, the spread of personal computers and the great diversification and refinement of methods have allowed for direct and experimental uses of quantitative analysis, even on a small corpus of data or from a micro-historical perspective. Widespread quantitative training would strengthen historians’ reflexive and interpretative skills.